2018
DOI: 10.1111/1748-5967.12284
|View full text |Cite
|
Sign up to set email alerts
|

Activity of glutathione S‐transferase and esterase enzymes in Helicoverpa armigera (Hübner) after exposure to entomopathogenic fungi

Abstract: Helicoverpa armigera, a polyphagous insect of crops and vegetables, is acquiring resistance against many commercial insecticides. The present study shows variations in the activity of two detoxification enzymes, namely esterase and glutathione S‐transferase (GST), in H. armigera after exposure to different isolates of entomopathogenic fungi. After treatment of larvae with the different isolates (Day 0), samples were collected on three days (Days 3, 5 and 7) for enzyme analysis. High GST activity was found in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…The activation or suppression of early-response genes is essential for host-pathogen interactions. We found that the early response was insu cient to overcome infection, which may re ect the suppression of genes known to participate in detoxi cation and fungal resistance encoding E4 and FE4 esterases, glutathione S-transferase, and UDP-glucuronosyltransferase (Bilal et al, 2018;Field and Devonshire, 1998;Xia et al, 2013). Conversely, two cathepsin B genes were upregulated in correlation with fungal infection in our study, as previously reported (Grell et al, 2011), and these may indeed act as detoxifying enzymes (Lan et al, 2021) (Fig.…”
Section: Fight Not Ight?supporting
confidence: 82%
“…The activation or suppression of early-response genes is essential for host-pathogen interactions. We found that the early response was insu cient to overcome infection, which may re ect the suppression of genes known to participate in detoxi cation and fungal resistance encoding E4 and FE4 esterases, glutathione S-transferase, and UDP-glucuronosyltransferase (Bilal et al, 2018;Field and Devonshire, 1998;Xia et al, 2013). Conversely, two cathepsin B genes were upregulated in correlation with fungal infection in our study, as previously reported (Grell et al, 2011), and these may indeed act as detoxifying enzymes (Lan et al, 2021) (Fig.…”
Section: Fight Not Ight?supporting
confidence: 82%